(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the syncretic features of the modernization of school education in the conditions of New Uzbekistan and the socio-philosophical aspects of this process. The article studies the combination of traditional and modern approaches in the education system, the integration of national and global values, as well as the impact of these changes on social consciousness and spirituality in society.